Typology and evolution of poverty in the world 1979-2021 (Research, Society and Development, 2024)
Poverty is a condition of lack inhuman beings, at first, it was only attributed to the scarcity of monetary income. But upon observing that individuals, sometimes, despite having said income, were still unable to satisfy their basic needs (food, clothing, housing, etc.), poverty began to be studied considering other variables, until reaching to current measurements that even transcend material aspects, such as freedom, capabilities, and opportunities. This work aims to give a general overview of the types of poverty and its behavior in the world. And it attempts to demonstrate theoretically the complexity of this concept and its relativity, in the face of a changing and heterogeneous society, through descriptive documentary research.